Transforming Expository Writing Skills in Class V Students: The Impact of the 'Modeling the Way' Method on Learning Outcomes - Rosmini Madeamin; Siti Suwadah Rimang (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the effect of the application Modeling the Way learning methods to the learning outcomes of fifth grade students.. This study refers to 3 indicators namely; 1) the achievement of completeness of learning outcomes, 2) student activity in learning activities has increased, 3) students respond positively to the implementation of learning using the Modeling the Way method. The research design uses The One Group Pretest-Posttest Design. Sampling using a proposive sampling technique. The population is the fifth-grade students with a research sample are 35 students of VB class. The study was conducted during 6 meetings. Data collection techniques using tests to measure learning outcomes before and after following learning by using the Modeling the Way learning method, observation sheet activities of students to observe student activities during the learning process, questionnaire responses of students to find out their responses to the implementation of learning using the Modeling method Way. The results showed that the average score of the initial test (Pretest) was 50.17 and there were 4 students (11%) who completed it, while the average score of the final test (Posttest) was 83.11 and there were 33 students (94%) in the complete category. Thus, it is evident that the use of the Modeling the Way method affects the learning outcomes of writing skills in the exposition paragraphs of fifth grade students of SD Inpres Mangga Tiga Makassar City.